Driving Higher Education Key Performance through Practitioner-Led Kampus Merdeka Curriculum: Integrating Religious–Social Values and Student Engagement - Ridho Fahlevi; Januar Iskandar (Al Mabhats : Jurnal Penelitian Sosial Agama, 2025)
The challenges facing higher education in the modern era necessitate graduates who are not only academically and professionally excellent but also possess moral integrity and social awareness. This research aims to analyze the implementation of a Practitioner Lecture program, founded on religious-social values, within the Merdeka Belajar Kampus Merdeka (MBKM) program. Furthermore, it seeks to examine this program's contribution to enhancing the Key Performance Indicators (IKU) of UNISKA Banjarmasin and improving the quality of student engagement. Utilizing a qualitative case study approach, this study is expected to identify how the explicit integration of values such as trustworthiness (amanah), justice, empathy, and social responsibility into the curriculum and practical learning processes facilitated by practitioners acting as role models can transform the MBKM experience. Anticipated findings suggest that this strategy significantly boosts the university's IKU, particularly in terms of graduate relevance and community service, while simultaneously fostering greater student motivation, responsibility, and the quality of their participation in MBKM activities. The conclusion of this research will underscore that a Practitioner Lecture approach grounded in religious-social values is capable of producing graduates who are not only competent but also possess noble character, prepared to serve as positive agents of social change, thereby offering a strategic model for higher education institutions to integrate scientific knowledge and religious principles for the betterment of society